Nisbah Daun Batang, Nisbah Berat Daun dan Nisbah Akar Tajuk Tanaman Sawi Pagoda (Brassica narinosa L.) Akibat Pemberian Pupuk Organik Cair Kascing, Papua Nutrient dan MA-11 - Ivonne Fitria Mariay; Bayu Imam Segoro; Veronica Leonora Tuhumena (Fakultas Pertanian Universitas Papua, 2022)
Analysis of the growth of the Shoot Root Ratio, Stem Leaf Ratio and Leaf Weight Ratio on pagoda mustard plants are expected to provide an accurate picture of growth and yields. The aim of the study was to determine and analyze the growth of the shoot-root ratio, stem leaf ratio and leaf weight ratio of pagoda mustard greens (Brassica narinosa L.) due to the administration of liquid organic fertilizer Kascing, Papua Nutrient and MA-11. This research is held at the screen house of the Department of Soil Science, Faculty of Agriculture, University of Papua for 2 months. The tools and materials used include: machetes, hoes, polybag shovels, digital scales, 30 cm ruler, stationery, trays seedling, notebook, medication label, sprayer, hand spray, 10 ml liquid measuring tube, oven, f1 pagoda mustard seed, Kascing, Papua Nutrient, MA-11, granulated sugar, vegetable pesticide nem oil, soil media, compost, manure goats and cows. There is a significant effect due to the application of Liquid Organic Fertilizer on the Root Root Ratio, Stem Leaf Ratio and Leaf Weight Ratio. Analysis of variance and further tests showed significantly different results between the control treatment and other treatments (P1, P2, and P3). The results of the 5% BNJ test were carried out by comparing the average difference between each treatment, both P0, P1, P2 and P3 with a critical value of 3.2. Treatment of P1 Liquid Organic Fertilizer vermicompost can be said to have the most significant effect on plant growth variables because it shows the ratio of absolute average prices is greater than the critical value.